Depression, sleep, body image, and lifestyle: Prevalence and associated factors of depression among school-going adolescents in Delhi National Capital Region - Tejasvini Khanna; Bratati Banerjee; Madan M. Majhi; Dheeman Futela (Indian Journal of Psychiatry)
Background: Adolescents are known to be vulnerable to depression, which worsened during the COVID-19 pandemic. They also exhibit poor sleep quality and body image issues (BIIs) which are considered risk factors for depression. There is a paucity of Indian studies regarding adolescent depression and its correlation with lifestyle. Aims: To detect the prevalence of depression in adolescents, and understand its association with sociodemographic variables, sleep quality, BIIs, and lifestyle factors. Materials and Methods: A cross-sectional study was conducted among 392 adolescents attending classes 8th–12th in two schools in Delhi National Capital Region. A pre-tested semi-structured questionnaire was used to collect sociodemographic and lifestyle data. Depression anxiety stress scale-21 was used to detect depression. Pittsburgh Sleep Quality Index and Stunkard Figure Rating Scale were used to evaluate sleep quality and BIIs. Data was analyzed using Statistical Package for Social Sciences Version-25. Results: Depression was present in 40.3% of students. It was more common in girls, older students, students in higher classes, who lacked siblings and whose mothers were engaged in professions as well as those with BIIs. However, after multivariate analysis, the association of depression with poor sleep quality, meal skipping, lack of exercise, family history of mental illness, and inverse association with open discussion of one’s thoughts and worries with family remained significant. Conclusions: Depression is common among adolescents and shows associations with poor sleep quality and lifestyle choices. Awareness of these associations may enable better screening and early intervention for vulnerable adolescents.